Analysis of milk marketing system : a case study of Pune, India - Pawar, Sangram Vilas; Datta, Avishek; Anal, Anil K.; Kuwornu, John K. M.; AIT Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2019)
India is the world largest producer and consumer of fresh milk, with 18% of the global market share. Almost 31% of the Indian population is vegetarian. Considering such a huge vegetarian population milk is one of the important sources of protein in India. India is among the fastest-growing milk market, with the estimated value of 6,671 billion INR (1 US$ = 71.15 INR). The Indian milk market is dominated by unorganized and informal marketing system, which is one of the major constraints in technology up-gradation and subsidizing dairy farmers in India. The specific objective of this study was: 1) To examine the factors influencing milk purchase decisions by the middle-class consumers in Pune city, 2) To examine the factors influencing middle-class consumer choices for certified pasteurized and uncertified unpasteurized milk in Pune city, and 3) To examine the factors influencing smallholder dairy farmers for the use of an unorganized milk marketing system. Structured questionnaires were used to interview 110 middle-class milk consumers in Pune city as well as 50 smallholder farmers in rural Pune (Nagapur village). The weighted average index (WAI) method was used to identify the factors influencing milk purchase decisions by middle-class consumers in Pune city. The bivariate probit regression model and binary probit model were used to identify the factors influencing middle-class consumer preferences for certified pasteurized and uncertified unpasteurized milk in Pune city. The weighted average index (WAI) method was used to examine the factors influencing smallholder dairy farmers for the use of unorganized milk marketing system. The results showed that gender, price, and availability of monthly payment facilities positively influenced the middle-class milk consumers decision to choose uncertified unpasteurized milk, whereas overall quality, ease of availability in the vicinity, fear of adulteration and advertisement, negatively influenced middle-class milk consumers{u2019} decision to choose of uncertified unpasteurized milk. The result also showed that higher price, instant cash policy, advance cash system, purchase price based on flat rates per liter and distance of market very strongly influence the smallholder dairy farmers for the use of an unorganized milk marketing system.
A Thesis submitted in partial fulfillment of the requirements for the degree of Master of Agribusiness Management
Thesis (M. Am.) - Asian Institute of Technology, 2019
Keywords: Dairy products industry -- India; Milk trade -- India